Pengaruh Media Pembelajaran Animasi Komputer Terhadap Hasil Belajar Ekonomi Siswa Kelas XI SMAN 1 Keruak: The Influence of Computer Animation Learning Media on Economics Learning Outcomes of Class XI Students at SMAN 1 Keruak - M. Saipul Watoni (Pendidikan Al-Gafari, 2025)
Teachers are required to be able to understand, master, and be able to use the available tools in an effort to achieve the expected teaching objectives. For that, teachers must have sufficient knowledge and understanding of learning media. This study aims to determine the effect of computer animation learning media on the learning outcomes of class XI students of SMAN 1 Keruak. This study was conducted at SMAN 1 Keruak. The research method used was a quasi-experimental study, involving 58 students of class XI IPS2 and XI IPS3 which were determined by cluster random sampling technique. Class XI IPS2 as the experimental class and XI IPS3 as the control class. The design of this study was a